2023
DOI: 10.3389/fpsyg.2023.1188344
|View full text |Cite
|
Sign up to set email alerts
|

What is the next structure? Guessing enhances L2 syntactic learning in a syntactic priming task

Abstract: Previous psycholinguistic research has shown that Second Language (L2) speakers could learn from engaging in prediction. Few works have directly examined the relationship between prediction and L2 syntactic learning. Further, relatively limited attention has been paid to the effects of two linguistic factors in this area: structure type and L2 proficiency. Using a mixed experimental design, 147 L2 Arabic speakers with varying L2 proficiency levels completed two syntactic priming experiments, each targeting a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…This explanation seems likely considering the results of a related study. Using the classic syntactic priming paradigm, an L2 Arabic priming study found immediate abstract priming for fronted TP in the priming phase for the control group although this priming effect did not sustain in the posttests (Alzahrani, 2023). This suggests that the method of presenting the prime may play a role in inhibiting (the present study) or triggering syntactic priming effects (Alzahrani, 2023).…”
Section: Story Primingmentioning
confidence: 52%
See 3 more Smart Citations
“…This explanation seems likely considering the results of a related study. Using the classic syntactic priming paradigm, an L2 Arabic priming study found immediate abstract priming for fronted TP in the priming phase for the control group although this priming effect did not sustain in the posttests (Alzahrani, 2023). This suggests that the method of presenting the prime may play a role in inhibiting (the present study) or triggering syntactic priming effects (Alzahrani, 2023).…”
Section: Story Primingmentioning
confidence: 52%
“…As such, intermediate learners may show abstract priming effects for more frequent structures but not for less frequent structures. For example, Arabic L2 speakers may show priming for the Double Object dative (DO) strucutre in the absence of a lexical overlap (Alzahrani, 2023), whereas a lexical overlap may be required for the priming of relative clauses.…”
Section: Related Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations